Mechanical and Electrical Behavior of Polymer Matrix Composite and their Hybrids Reinforced with (Carbon Black–Boron) Particles - Al-Khafaji, R S (Al-Nahrain Journal of Science, 2018)
The work is designed to study experimentally the mechanical and electrical behavior of polymer matrix composites and their hybrids which reinforced by carbon black particles with constant volume fraction (10)% and boron particles with different volume fractions (0,2,4,and 6)% which are bounded with unsaturated polyester resin. Number of mechanical tests were done, they include (hardness, Charpy impact,and bending strength), which done at room temperature in Iraq .Results of the work show that the values of hardness increased with volume fractions of boron powder ,the best values of impact strength and elasticity of modulus present at (4)% .On the other hand,dielectric constant (έ) decreases with increasing applied frequency, and alternating electrical conductivity(σa.c) increases as the applied frequency increases up to 1MHz, While (έ) and (σa.c) increased as increasing of temperature.